Seroprevalence of Anti-Leptospira IgG and IgM Antibodies and Risk Assessment of Leptospirosis among Urban Poor Communities in Kuala Lumpur, Malaysia - Sahimin, Norhidayu; Sharif, Siti Aishah; Mohd Hanapi, Izzah Ruzana; Nai Chuan, Sukchinda; Lewis, John Watkin; Douadi, Benacer; Mohd Zain, Siti Nursheena (American Society of Tropical Medicine and Hygiene, 2019)
Leptospirosis is a zoonotic bacterial disease caused by pathogenic species of the genus Leptospira. Disease incidenceisknowntobeattributed toenvironmental and social conditions which promote the spread ofreservoir hosts, primarily rodents. A well-being program was conducted to determine the seroprevalence and risk factors associated with leptospirosis inurban poor communities occupying low-cost flat accommodation and squatter settlements in the vicinity of Wilayah Persekutuan, Kuala Lumpur. Blood samples from a total of 532 volunteers were screened for the detection of IgG and IgM antibodies against leptospirosis using ELISA. Demographic data were collected for each participant through a questionnaire survey before blood collection. The overall seroprevalence was low (12.6%, n = 67/532; 95% CI: 9.9-15.7%), with 8.1% (n=43/532) being seropositive for anti-Leptospira Ig G, indicating previous infection, and 4.9% (n = 26/532) for anti-Leptospira Ig M, indicating current infection. Two significant factors such as host age (P ≤ 0.01) and knowledge of disease transmission (P = 0.017) significantly influenced the presence of anti-Leptospira Ig M, whereas the detection of anti-IgG indicated the presence of clean drinking water sources (P = 0.043). Despite the low prevalence, the transmission of leptospirosis does occur among urban poor communities, suggesting the need for undertaking public awareness programs. Copyright © 2019 by The American Society of Tropical Medicine and Hygiene.